The Impact of Digital Financial Inclusion on Residents’ Entrepreneurial Decisions - Yue, Lifei (Transactions on Economics, Business and Management Research, 2024)
As technology advances, digital inclusive finance has gradually become an important force supporting entrepreneurial activities. This paper, based on the Probit model, utilizes cross-sectional data from the China Family Panel Studies (CFPS) in 2020 to investigate the impact of digital inclusive finance on residents' entrepreneurship. The research reveals that digital inclusive finance promotes entrepreneurship among residents in China, a conclusion robustly supported by a series of sensitivity tests. Mechanism tests suggest that digital inclusive finance alleviates credit constraints during residents' entrepreneurial processes and enhances their participation in financial markets. Heterogeneity tests indicate that digital inclusive finance significantly stimulates rural residents' entrepreneurship, reflecting its inclusive nature. From a gender perspective, digital inclusive finance has a more substantial impact on male entrepreneurship, while its impact on female entrepreneurship is relatively minor. Furthermore, heterogeneity tests based on human capital suggest that digital inclusive finance reduces the human capital barrier required to entrepreneurship, thus facilitating residents with lower levels of education to engage in entrepreneurial activities. Hence, it is imperative to continuously deepen the popularization of digital inclusive finance while also addressing the entrepreneurial needs of vulnerable groups, thereby further unleashing residents' entrepreneurial vitality and achieving genuine inclusivity.